Influence of implant length and bone defect situation on primary stability after distal femoral replacement in vitro - Nadorf, Jan; Klein, Simon Benjamin; Gantz, Simone; Kretzer, Jan Philippe; Bischel, Oliver E. (The knee, 2017)
Background: Aseptic loosening is the major reason for failure of distal femoral replacement using current modular megaprostheses. Although the same stems are used for proximal and distal replacement, survival rates in clinical studies with distal reconstruction were lower within the same system compared to proximal reconstruction. We analyzed whether primary stability as presupposition for long-term fixation can be achieved with a current tapered stem design. Additionally, we hypothesized that stem length affects primary stability depending on bone defect situations. Methods: A modular tumor system (Megasystem-C®, Link GmbH, Hamburg, Germany) with two different tapered stems (100 and 160mm) was implanted in eight Sawbones® in two consecutively created defect situations (10 and 20cm proximal to knee joint level). Primary rotational stability was investigated by measuring relative micromotions between implant and bone to identify the main fixation areas and to characterize the fixation pattern. Results: The fixation differed between the two stem lengths and with respect to both defect situations; however in each case the main fixation area was located at or close to the femoral isthmus. Highest relative micromotions were measured with the 160-mm stem at the distal end within small bone defects and at the proximal end when defects were increased. Conclusions: The analyzed design seemed to create sufficient primary stability along the main fixation areas of the implant. Based on these results and with respect to oncologic or potential revision situations, we suggest the use of the shorter stem to be more favorable in case of primary implant fixation.